Microsoft Server 2008 server administration (exam 70-646) - Long, Mark.; Safari eBooks ([S.l.] : Virtual Training Co., 2006)
"A server administrator is responsible for the operations and day-to-day management of an infrastructure of servers for an enterprise organization. Windows server administrators manage the infrastructure, Web, and IT application servers. Holding a premier, industry standard certification like the MCITP on Microsoft's Windows Server 2008 platform clearly demonstrates an ability to provide professional level server administration to large and mid-sized companies. In this course, Microsoft Certified Trainer Mark Long teaches you the technologies you need to know to help prepare for the MS 70-646 Pro: Windows Server 2008, Server Administrator exam. Passing this exam (after passing exams 70-640 and 70-642) will earn you the Server Administrator MCITP certification. Work files are included. To begin learning today, simply click on the movie links." --Resource description page.
Title from resource description page (viewed July 25, 2011).
Presenter, Mark Long.
Keywords: Client/server computing; SQL server; Database management; Computer technicians -- Certification; Electronic books